2020
DOI: 10.1186/s12859-020-3505-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Escherichia coli strains to oxidative stress are reflected in properties of their structural proteomes

Abstract: Background: The reconstruction of metabolic networks and the three-dimensional coverage of protein structures have reached the genome-scale in the widely studied Escherichia coli K-12 MG1655 strain. The combination of the two leads to the formation of a structural systems biology framework, which we have used to analyze differences between the reactive oxygen species (ROS) sensitivity of the proteomes of sequenced strains of E. coli. As proteins are one of the main targets of oxidative damage, understanding ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 121 publications
0
10
0
Order By: Relevance
“…to absorb oxidative damage 41,42 . This may explain the differential upregulation in amino acid pathways, particularly when superoxide (and its by-product ROS) is removed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…to absorb oxidative damage 41,42 . This may explain the differential upregulation in amino acid pathways, particularly when superoxide (and its by-product ROS) is removed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that bacteria have adapted the ability to assemble amino acids to counter ROS effects. For example, prioritising methionine/cysteine on the surface of cytosolic proteins can act as “sponges” to absorb oxidative damage 41, 42 . This may explain the differential upregulation in amino acid pathways, particularly when superoxide (and its by-product ROS) is removed.…”
Section: Resultsmentioning
confidence: 99%
“…In E.coli , amino acid synthesis pathway is known to be very sensitive to oxidative stress as enzymes involved in amino acid biosynthesis are susceptible to oxidative damage ( Mih et al, 2020 ). It can also represent the intensified use of these amino acids towards mediating a response to TCNP treatment.…”
Section: Resultsmentioning
confidence: 99%
“…23 Previous studies have shown that in the pathophysiological processes of enteric bacterial infections, various defence mechanisms of the immune system are activated that promote the appearance of ROS (phagocytosis), and consequently induce cell death of the infectious agent. 22,24,25 As a result of an evolutionary convergence of the mechanisms of elimination of bacterial infections and the survival of infectious microorganisms, these generate adaptive processes that avoid oxidative stress. It is known that KatG and AhpF proteins enable the removal of intracellular hydrogen peroxide in bacteria, thus reducing the oxidative stress, which explains why a higher concentration of these proteins is found in Enterobacterales after being exposed to blue lightassociated photodynamic therapies.…”
Section: Discussionmentioning
confidence: 99%